Hubungan Konsep Diri dan Self-Esteem Terhadap Kepercayaan Diri pada Atlet Panjat Tebing Ditinjau Dari Jenis Kelamin: Penelitian - Irma Martitin; M.Zuhdi Zainul Majdi; Hasaniah Zulfiani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine how self-concept and self-esteem influence athletes’ self-confidence, with gender as a moderating variable. Using a correlational design, the research involved 110 active athletes in West Nusa Tenggara, consisting of 55 males and 55 females selected through purposive sampling. The instruments used were the Self-Concept Scale, Self-Esteem Scale, and Athlete Self-Confidence Scale, all of which had been tested for validity and reliability. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) to assess the relationships among variables as well as the moderating role of gender. The findings revealed that both self-concept and self-esteem significantly influenced athletes’ self-confidence, and their combination simultaneously contributed to a stronger effect. However, gender did not moderate the relationship, indicating a similar pattern between male and female athletes. These results highlight that self-confidence is more strongly shaped by internal psychological factors rather than gender differences, suggesting that training programs emphasizing the strengthening of self-concept and self-esteem are essential to enhance athletes’ mental readiness and optimize performance.